APLIKASI PENGELOLAAN KEGIATAN KAMPUS BERBASIS MOBILE MENGGUNAKAN METODE AGILE - Manalu, Ester; Simbolon, Yoel; Manihuruk, Rifaldi; Napitupulu, Virzinia; Surbakti, Efrans; Lumbanbatu, Vio (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Students in the campus environment often miss important information conveyed through WhatsApp or unstructured communication media. In addition, lecturers are not always able to monitor every message in the group, causing announcements to get lost among many other messages. This issue requires a solution in the form of a centralized and efficient campus activity management application. This application aims to make it easier for lecturers to deliver announcements directly and in an organized manner, while also serving as an integrated platform that supports communication between lecturers, students, and campus administration. The methodology used in this study includes internal data analysis based on daily operational observations on campus, as well as consultations with lecturers and students without involving surveys or questionnaires. The analysis is conducted to assess the technical, economic, operational, legal, and scheduling feasibility of the application development.The results of this study show that this application is feasible to develop using React Native for cross-platform development, Java script for the backend, and Firebase as the database. This application is also designed to comply with data security and privacy standards in accordance with regulations in Indonesia. With a simple and user-friendly interface, this application is expected to facilitate information delivery, save time, and improve the efficiency of campus activity management.